Filtering carbon dioxide through carbon nanotubes - Mantzalis, Dimitrios; Asproulis, Nikolaos; Drikakis, Dimitris (Elsevier Science B.V., Amsterdam., 2011)
Layering phenomena of carbon dioxide transported through carbon nanotubes are investigated through molecular dynamics simulations. The layering formation is examined for carbon nanotubes spanning from (8,8) to (20,20) subjected to pressures and temperatures that range from 1 to 20 bar and 300 to 400 K, respectively. Well defined layers are developed around the internal and external surface of the nanotubes for all the examined cases. It is shown that the number of layers along with their relative strength varies as a function of the nanotube's diameter, size, carbon dioxide density and gas-structure interactions.
Keywords: molecular-dynamics hydrogen storage gas separation critical co2 adsorption bundles size temperature simulations transport